Possible Roles of IL-33 in the Innate-Adaptive Immune Crosstalk of Psoriasis Pathogenesis - Cannavò, Serafinella Patrizia; Bertino, Lucrezia; Di Salvo, Eleonora; Papaianni, Valeria; Ventura-Spagnolo, Elvira; Gangemi, Sebastiano (Mediators of Inflammation, 2019)
Background. IL-33 belongs to the IL-1 family, playing a role in several biologic processes as well as in the pathogenesis of different diseases, including skin pathologies. It acts as an alarmin, released by damaged cells. Binding to a ST2 receptor, it stimulates many immune cells such as ILC2 and Th2 cells. IL-33/ST2 axis seems to be involved in Th17 response. According to this, a review was performed to analyze if IL-33 even interplay in the onset of psoriasis, a Th1/Th17 inflammatory disease. Methods. Data obtained from the included articles are study author name, publication date, group studied, clinical and biological variables, laboratory tests, and outcome of interest of the study. Results. Data are obtained from the 19 studies identified, which assessed the association between IL-33 and psoriasis. Discussion. It seems to promote the innate-adaptive immune crosstalk: it could induce mast cells and neutrophil response after being released by injured keratinocytes and after stimulation by some cytokines, in particular TNFα, INFγ, and IL-17A. In addition, it seems to be involved from the onset of disease to the development of comorbidities, as psoriatic arthritis. Conclusion. The core of the future research on psoriasis could be to fully understand the role of this complex cytokine, in order also to find a new therapeutic approach.